(untitled) (Archives of Clinical and Medical Case Reports, 2018)
Introduction: Effective communication skills that foster responsible sexual decisions are known to have the potential to reduce the risky adolescent sexual behavior. It is well understood that maternal communication is a key element in modifying the adolescent sexual behavior. The objective of this qualitative study was to explore if Puerto Rican mothers of adolescent girls have conversations about sexuality with their daughters and the content of such conversations. Methods: A total 22 HIV-seropositive mothers and 22 HIV-seronegative mothers were enrolled. Six focus groups were conducted, sessions were transcribed ad-verbum and coded for specific topics. All qualitative analysis was incorporated into Atlas.ti. Results: Participants in both groups had a similar average age (mean=41 years old); but, the HIV-seropositive mothers were more likely single, less educated and unemployed. Regarding having engaged in conversations about sexuality and the topics covered, however, there were no differences revealed among HIV-seropositive mothers and seronegative mothers. In both groups, mothers understood the importance of these conversations, but most said they were difficult and uncomfortable. Conclusion: These findings reinforce the importance of communication between mothers and daughters for the prevention of STIs, HIV/AIDS, and teenage pregnancy in minority populations. Interventions are needed for mother and daughter to improve communication skills, communication about sexuality, and addressing prevention.